Sustainable Strategies for Urban Waste Management: Examining the Implementation of the ‘Broh Jeut Keu Peng’ Public Policy in Lhokseumawe City - Risna Dewi; Maisyura Maisyura; Dwi Fitri; Amirul Hanif (Pencerah, 2025)
This study examines strategies for sustainable urban waste management through the implementation of the “Broh Jeut Keu Peng” (Waste Becomes Money) policy in Lhokseumawe City. Introduced through Qanun No. 1 of 2015 on Waste Management, the policy aims to address persistent challenges, including inadequate infrastructure, low community participation, and weak stakeholder coordination. Using a descriptive qualitative approach, data were collected through interviews, field observations, and document analysis to explore how the policy is being translated into practice. The findings reveal that despite having strong legal legitimacy, the policy remains in its early implementation phase. Benchmarking activities, such as visits to Banyumas, an area known for its advanced waste management system, have been conducted, but concrete actions in Lhokseumawe are still limited. The policy outlines four strategic components: (1) educational efforts promoting the 3R concept and environmental awareness grounded in local culture; (2) technical and infrastructural improvements, including strengthened TPS facilities, transportation fleets, and area-based TPS3R development; (3) economic incentives through waste banks, compost production, and reward-and-punishment mechanisms; and (4) collaborative engagement involving government bodies, community leaders, religious figures, the informal sector, and private stakeholders. In conclusion, the “Broh Jeut Keu Peng” policy holds strong potential for sustainable waste management, but its success requires effective implementation, improved facilities, consistent public education, and coordinated multi-actor collaboration.